Quality assessment of Clinical Practice Guidelines for the management of paediatric dental emergencies applicable to the COVID-19 pandemic, using the AGREE II instrument. A Systematic Review (2020)
Objective: To assess the quality of Clinical Practice Guidelines (CPG) related to the management of paediatric dental emergencies applicable to the COVID-19 pandemic, through the use of the measuring instrument AGREE II (Appraisal of Guidelines for Research and Evaluation in Europe). Sources and Data collection: A rigurous online search of CPG was accomplished among the main CPG compilers: National Institute for Health and Care Excellence (NICE), National Guideline Clearinghouse, Agency for Healthcare, Research and Quality (AHRQ), Andalusian Health Technology Assessment Department (AETSA), American Academy of Family Physicians, Tripdatabase. Furthermore, because of the need to identify CPG that meet the inclusion criteria, a manual search, among the main national and international dental organizations as well as recognized web sites, was also accomplished. Selection of research studies: All of the guides focused on paediatric dental emergencies, available in the database and “gray” literature, and published between 2000 and 2020 (applicable to COVID-19 pandemic) were included without any language restrictions. The CPG that did not contain the full paper or were addressed to adults or children with special needs, were excluded from the selection. The evaluation of the CPG, independently included, were achieved by four (04) experts by using AGREE II. Results: Five (05) out of twenty-three (23) selected CPG, were classified as “acceptable” according to AGREE II. These five guides were evaluated to determine their “Recommendation degree”. Only one (01) CPG “Guía Clínica AUGE de Urgencias Odontológicas AmbulatoriasChile, 2011” reached a score of 75%, the highest among the other guides (5 domains with a score >= 60%, including the domain III “Rigour of Development”) to be considered as a “highly recommended” CPG. Conclusions: According to the quality assessment and recommendation degrees criteria from AGREE II, high, middle and low quality CPG were identified. Only one CPG reached a score of 75%, to be classified as “highly recommended”. Therefore, it is suggested that the existing CPG updates and future CPG use the available tools and methodologies during their elaboration, in order to guarantee their quality. Clinical significance: High quality CPG for the management of dental emergencies are designed to support dental health professionals in decision-making to adopt specific dental procedures in the current COVID-19 pandemic. As a matter of fact, these CPG might contribute to reduce the risk of transmission, in case of fresh outbreak of the illness. Likewise, they might help to determine which cases warrant medical attention in centres with special facilities for COVID19.